2011
DOI: 10.3310/hta15080
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised controlled trial and economic evaluation of ion-exchange water softeners for the treatment of eczema in children: the Softened Water Eczema Trial (SWET)

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 22 publications
0
69
1
Order By: Relevance
“…A similar approach was successfully used in the HTA-funded Softened Water Eczema Trial in which the nurses were inadvertently unblinded in just 3.5% of cases (11/316). 356 Packaging, labelling and distribution of clothing will be performed by staff at the co-ordinating centre and sent to participants by first-class post. Although it will not be possible to blind participants to their treatment allocation, efforts will be made to minimise expectation bias by emphasising in the trial literature that the evidence supporting the use of silk clothing for eczema is currently limited and that we do not yet know if this clothing offers any benefit over standard care.…”
Section: Randomisation and Blindingmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar approach was successfully used in the HTA-funded Softened Water Eczema Trial in which the nurses were inadvertently unblinded in just 3.5% of cases (11/316). 356 Packaging, labelling and distribution of clothing will be performed by staff at the co-ordinating centre and sent to participants by first-class post. Although it will not be possible to blind participants to their treatment allocation, efforts will be made to minimise expectation bias by emphasising in the trial literature that the evidence supporting the use of silk clothing for eczema is currently limited and that we do not yet know if this clothing offers any benefit over standard care.…”
Section: Randomisation and Blindingmentioning
confidence: 99%
“…This approach has been successfully used by the study team in a previous eczema trial. 356 l Adherence, acceptability and tolerability of the garments as assessed by children and parents/carers in participant diaries [for the intervention group during the 6 month RCT and by questionnaire at 8 months (for both groups)]. These issues will also be explored in more detail through focus group discussions with trial participants.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies have shown factors such as urban living and proximity to pollution may modify one's risk of developing AD [ 48,62 ] . Exposure to hard water had been associated with a higher prevalence of AD, but a recent randomized controlled trial failed to fi nd utility in water softeners as an adjunct to AD therapy [ 74 ] . Repeated skin exposure to water and detergents during infancy has also been proposed as a cause of the increasing prevalence of AD [ 53 ] .…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The role of soaps and detergents remains unproven [ 10 ] , although alkaline soaps dissolve the lipid bilayer and increased pH results in up-regulation of serine protease activity and an increase in epidermal cell desquamation and dryness [ 2 ] , so the use of soap substitutes seems sensible despite a lack of confi rmatory evidence [ 14 ] . Hard water has been thought to be a cause of dry skin and eczema, but a recent UK study [Softened Water Eczema Trial [SWET]] on the use of water softeners in hard water areas did not show any overall statistical signifi cance to justify their use in treating eczema [ 15 ] .…”
Section: Environmental Factors Causing Dry Skin In Eczemamentioning
confidence: 99%